An enhanced-performance CMOS imager with a flushed-reset photodiode pixel. - Pain, B. (IEEE Transactions on electron devices)
A new front-end for photodiode-based CMOS imagers is presented. Degradation in imaging performance due to conventional hard- and soft-reset of pixels is analyzed. To overcome these limitations, the design and operation of a flushed-reset pixel is described. The flushed-reset pixel combines the best of hard- and soft-reset to simultaneously provide excellent radiometric accuracy, high linearity, no image lag, high saturation level, and reduced read-noise. The new front-end is implemented by changes to the column-circuitry only, leaving the pixel unchanged, preventing degradation of any unrelated imaging performance. It is compatible with large format imager implementation, has minimal impact on the frame-rate, and does not introduce any additional hot-carrier stress in the pixel. Data from a large format (5122) imager demonstrates the efficacy of the flushed-reset pixel approach.